Business Process Governance: Theorizing and Empirical Application - Niehaves, Björn; Plattfaut, Ralf; Budde, Max; Becker, Jörg (17th Americas Conference on Information Systems (AMCIS 2011), 2011)
Studies by Gartner (2010) or McKinsey (2008) suggest univocally that improving business processes is the undisputednumber one priority for organizations world-wide. Hence, organizations need adequate capabilities for Business ProcessManagement (BPM). However, these capabilities do not necessarily need to be developed in the organization itself – aninclusion using other sourcing structures (e.g. cooperation/network or market instead of hierarchy) is possible as well. Thispaper builds upon an understanding of BPM as a dynamic capability and a well-known distinction of governance strategies(market, cooperation, hierarchy) to develop a business process governance framework. Using an extensive case study weinitially test this framework in a European PRODUCTION company. Therefore, we make the following contributions: 1)development of a BPM theory that integrates dynamic capability and governance theory, 2) a model for understandingsourcing strategies in BPM, and 3) empirically sound factors explaining sourcing strategies in BPM. Our results suggest thatorganizations facing a low dynamic market environment do not employ dedicated resources for business process change butrely on ad-hoc measures. Moreover, they gather these resources mostly internally (hierarchical governance). The paper endswith implications for both research and practice, limitations, and potential avenues for future research.